Relevance of glomerular c4d deposition in pediatric patients with henoch-schönlein purpura compared to IgA nephritis - Benz, Kerstin; Ferrazzi, Fulvia; Galiano, Matthias; Sauerstein, Katja; Vonbrunn, Eva; Daniel, Christoph; Büttner-Herold, Maike; Amann, Kerstin Ute (Journal of Nephropathology, 2021)
Introduction: IgA nephropathy (IgAN) is the most common primary glomerulonephritis (GN) in western countries and Henoch-Schönlein purpura nephritis (HSPN) is the most common form of vasculitis in childhood. Renal biopsy findings in both nephropathies are often similar and are characterized by mesangioproliferative GN with mesangial or mesangiocapillary IgA and C3c deposits. Objectives: The aim of this study was to investigate the significance of glomerular C4d-deposition as a discriminating factor between pediatric HSPN and IgAN. Patients and Methods: We retrospectively analyzed patient records and renal biopsies from 53 pediatric patients from one single center with a median age of 10.5 years (range 2.3-18 years). Twenty-two patients suffered from IgAN and 31 from HSPN. Work-up of all renal biopsies was performed using standard protocols including immunohistochemistry for C4d. Results: Pediatric IgAN patients presented significantly more often with gross hematuria, higher serum creatinine, lower glomerular filtration rate, lower serum C3 and proteinuria and on histology less endocapillary hypercellularity compared to HSPN patients. However, the rate of glomerular C4d-positivity was not different between IgAN (36%) and HSPN (42%). Comparing all cases with positive versus negative glomerular C4d-staining, pediatric patients with glomerular C4d-positivity showed significantly lesser gross hematuria and received significantly more often cyclophosphamide. This was in line with a tendency towards more proteinuria, hypertension and renal insufficiency at last follow-up in C4d-positive compared to C4d-negative patients. Conclusion: In conclusion, in our monocentric study glomerular C4d does not differ between pediatric HSPN and IgAN, but was associated with a tendency to a more severe course of the disease that needs to be confirmed in larger multicentric studies.
CRIS-Team Scopus Importer:2021-01-22
Keywords: C4d staining; Glomerulonephritis; Henoch-Schönlein purpura; IgA nephritis; IgA vasculitis; Pediatric nephrology